Research on E-Closed-Loop Supply Chain Decision-Making Considering Service Competition and Government Under Different Platform Recycling Modes - Xia, Yuntian (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Considering an E-closed-loop supply chain consisting of a producer, the competing resell e-commerce platforms and a third-party platform, under the government subsidy mechanism, by constructing game models under four scenarios, the influence of different platform reusing modes and facility level competition intensity on the optimal tactical choice of the E-closed-loop supply chain is compared and then analyzed. The study found that: (1) Under the mode of resale e-commerce platform recycling-government subsidy to resale e-commerce platforms, the profits of producers and resell e-commerce platforms are the highest, while under the mode of third-party platform recycling-government subsidy to the manufacturer, the profit of the producer is lowest. (2) When the degree of competition in the service level of resell e-commerce platforms is low, the service level is highest in the mode of government-subsidized recycling by resell e-commerce platforms. When the degree of competition is high, the service level provided by resell e-commerce platforms is the highest in the form of third-party platform recycling-government support to the producer. (3) As the recycling cost of producers increases, the order amount of products, the recycling rate of products and the number of recycled used products continue to increase.